Lingkungan Kerja Non Fisik, Motivasi Prestasi, dan Disiplin Preventif Terhadap Kinerja Pegawai (Studi Kasus Pada DPRD Kabupaten Grobogan Tahun 2022) - Ida Wahyuningsih; Dita Prameswari (LPPM Universitas An Nuur, 2024)
Background: In the era of globalization, development is increasingly rapid so that an organization must innovate to improve the performance of its employees. Based on case studies in the Grobogan Regency DPRD, there are still employees who are late and go home before their time to go home. So that it has an impact on other employees who imitate this behavior. With these problems, it is necessary to pay attention to how to maintain stable organizational performance. In implementing good human resources by prioritizing employee performance as the driving force of the company. Several factors that can influence employee performance include the non-physical work environment, achievement motivation, and preventive discipline.Methodology: The object of this research is all Grobogan Regency DPRD employees who are the population in this research. while the sampling method used census techniques for 143 respondents. then data is collected through a questionnaire which will be processed using SPSS 24.0Results: The research results show that the non-physical work environment has a positive and significant influence on employee performance. Achievement motivation has a positive and significant influence on performance. And preventive discipline has a positive and significant effect on employee performance.Conclusion: The non-physical work environment, achievement motivation and preventive work discipline play a role in improving employee performance.